Methodology of Monitoring Social and Economic Development in Regional Economic Systems (illustrated by the Altay Area) - O. I. Kuznetsov (Вестник Российского экономического университета имени Г. В. Плеханова, 2024)
The article studies such notions as ‘methodology’, ‘regional economic system’, ‘monitoring of regional economic system’. The author provides his own definition of the notion ‘monitoring of social and economic development of regional economic systems’ and highlighted 6 key stages of its conducting: organizational, information collection, information preparation, data analysis, forecasting and modeling, conclusion preparation and their publication. As an example of monitoring the author chose a regional program, which affects directly the development of social component of the regional economic system, in particular, the achievement of high standard of living at the expense of cutting poverty rate and raising real income of the population. The author conducted analysis by the proposed methodology using open sources of information. In this analysis he used the method of standard values with estimation of the program implementation efficiency. On the basis of monitoring results a conclusion was drawn about the efficiency of the given regional program in the Altay area in view of high figures of efficiency by set goals and indicators of the regional program.